Enhancing Transparency and Fairness in Digital Lucky Draws Using Smart Contracts - Tony Tan; Andrian Andrian; Fredian Simanjuntak (Universitas Bandar Lampung (UBL), 2025)
Traditional lucky draw systems often face trust issues due to a lack of transparency and potential for manipulation. This study addresses these challenges by developing and evaluating a blockchain-based lucky draw prototype named